Function and expression pattern of terminal flower 1(TFL1) homolog genes in dicot plants. - Tahery, Yaghoob; Ab Shukor, Nor Aini; Abdul Hamid, Hazandy; Abdullah, Mohd Puad; Baseruddin, Norlia; Kafilzadeh, Farshid (IDOSI Publication, 2010)
Terminal ﬂoweringl (TPLI) is a key gene in charge of ﬂowering time inArabz'dopsz's thaliana. During the past decade, genetic studies have found out several TFL] like genes in dicot plants. The main issues addressed in this paper are current advances in TFL] homologs isolated from different dicot species and their function in ﬂowering. Taking advantage of previous studies of cloning, in this paper we have evaluated function of these genes in regulating flowering time. It will then go on to place or parts of plants in where these genes express. Moreover, similarity and differences between them and other known genes, have been compared.